Sequence-specific retrotransposition of 28S rDNA-specific LINE R2Ol in human cells - Su, Yuting (RNA, 2019)
R2 is a long interspersed element (LINE) found in a specific sequence of the 28S rDNA among a wide variety of animals. Recently, we observed that R2Ol isolated from medaka fish, Oryzias latipes, retrotransposes sequence specifically into the target sequence of zebrafish. Because the 28S target and flanking regions are widely conserved among vertebrates, we examined whether R2Ol can also integrate in a sequence-specific manner in human cells. Using adenovirus-mediated expression of R2Ol constructs, we confirmed an accurate insertion of R2Ol into the 28S target of human 293T cells. However, the R2Ol mutant devoid of endonuclease (EN) activity showed no retrotransposition ability, suggesting that the sequence-specific integration of R2Ol into 28S rDNA occurs via the cleavage activity of EN. By introducing both R2Ol helper virus and donor plasmid in human cells, we succeeded in retrotransposing an exogenous EGFP gene into the 28S target site by the trans-complementation system, which enabled simplification of specific gene knock-in in a time-efficient manner. We believe that R2Ol may provide an alternative targeted gene knock-in method for practical applications such as gene therapy in future.